Grundtvig om folkekirken på Den grundlovgivende Rigsforsamling i 1849 - Grundtvig, N. F. S. (Grundtvig-studier, 1987)
Grundtvig on the Danish Church is a reprint of Grundtvig’s speech in the Constitutional Assembly of 1849 according to the short-hand minutes recorded in the Assembly’s Gazette. Here he gives his reasons for not supporting the paragraph on the Church in the Constitution Bill including in his arguments a comparison with the position of the Established Church in England. He wanted complete freedom of worship in Denmark, while welcoming that the State subsided the form of worship favoured by a large majority of the population, as long as they did so out of their own free will. He also proposed that any member of the Danish Church might approach any member of its clergy about baptism, communion and confirmation. Among those who took issue with him was J. P. Mynster, Bishop of Zealand, though, as it stood, he could not vote for the Constitution Bill either